RESPONDING TO MASS ATROCITIES: TRACING THE ORIGINS AND REFLECTINGON THE EVOLVING ROLES OF THE RESPONSIBILITY TO PROTECT ANDINTERNATIONAL CRIMINAL COURT (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2025)
The Responsibility to Protect (R2P) and the International Criminal Court (ICC) share a common moral foundation rooted in the post-WWII human rights agenda. They constitute the response of the international community to mass atrocities around the world. R2P, as a political and normative framework, seeks to ensure that states uphold their duty to protect populations from genocide, crimes against humanity, war crimes and ethnic cleaning, and the ICC as an independent judicial mechanism, aims to prosecute and try those individuals alleged to have committed mass atrocity crimes. This paper traces the historical foundations of both frameworks, shared objectives and conceptual complementarities that underpin their roles in atrocity prevention and response. It also explores the tensions that have emerged in their interaction, particularly in the face of political realities, issues of sovereignty and challenges of contested implementation. It further analyzes how the functions and relevance of R2P and ICC have evolved over time, how they have affected the response to more recent conflicts and how these developments have influenced their overall effectiveness. By situating R2P and the ICC within the broader architecture of atrocity prevention and accountability, the paper aims to offer a nuanced understanding of their interplay and propose pathways for enhancing their coherence and impact in the face of ongoing and future mass atrocities.Keywords: Responsibility to Protect, International Criminal Court, Prevention, Accountability, Atrocity Crimes, Justice, Peace